Hydrology Analysis and Rainwater Harversting Effectiveness as an Alternative to Face Water Crisis in Bantan Tua Village Bengkalis District-Riau - Cahyaningsih, Catur (-)
Home residence around Bantan Tua Village, Batan Subdistrict, Bengkalis District, Riau Province, have a tub for Rain Water Harvesting (PPAH), to collect and store water when rain come for cooking and drinking purposes. PPAH tub at home residence has a variety of sizes. There is a tub that size is too large and too small. PPAH tub volume size must be adapted to the rainfall data to be able need supply for community. The fundamental problem is that most people do not know the effective size PPAH tub to accommodate the abundance of rainfall harvesting because limited rainfall data information and the using of formulas hydrology calculation. Based on rainfall data in Bengkalis 2014, the average runoff of rain water per month is 141.5 mm. Houses the size of 8 x 10 m, which is the dominant type of house in Bengkalis, the ideal amount of rainwater collected in each house is 1920 m2 / month. While water demand required by equating averaged, the house is a consisting of four members is 3600m3 / month. End of month, volume of tub has deficiency is 1600m3. Recommendation of effective PPAH tube is 1500 liters, based on data rainwater runoff per month.